The Foxb1-expressing neurons of the ventrolateral hypothalamic parvafox nucleus project to defensive circuits - Bilella, Alessandro; Alvarez-Bolado, Gonzalo; Celio, Marco R. (The journal of comparative neurology, 2016)
The parvafox nucleus is an elongated structure that is lodged within the ventrolateral hypothalamus and lies along the optic tract. It comprises axially located parvalbumin (Parv)-positive neurons and a peripheral cuff of Foxb1-expressing ones. In the present study, injections of Cre-dependent adenoviral constructs were targeted to the ventrolateral hypothalamus of Foxb1/Cre mice to label specifically and map the efferent connections of the Foxb1-expressing subpopulation of neurons of the parvafox nucleus. These neurons project more widely than do the Parv-positive ones and implicate a part of the axons known to emanate from the lateral hypothalamus. High labeling densities were found in the dorsolateral and the upper lateral portion of the periaqueductal gray (PAG), the Su3 and PV2 nuclei of the ventrolateral PAG, the cuneiform nucleus, the mesencephalic reticular formation, and the superior colliculus. Intermediate densities of terminals were encountered in the septum, bed nucleus of the stria terminalis, substantia innominata, various thalamic and hypothalamic nuclei, pedunculopontine nucleus, Barrington's nucleus, retrofacial nucleus, and retroambigual nucleus. Scattered terminals were observed in the olfactory bulbs, the prefrontal cortex and the lamina X of the cervical spinal cord. Because the terminals were demonstrated to express the glutamate transporter VGlut2, the projections are presumed to be excitatory. A common denominator of the main target sites of the Foxb1-positive axons of the parvafox nucleus appears to be an involvement in the defensive reactions to life-threatening situations. The hypothalamic parvafox nucleus may contribute to the autonomic manifestations that accompany the expression of emotions. J. Comp. Neurol. 524:2955-2981, 2016. © 2016 Wiley Periodicals, Inc.